2011
DOI: 10.1111/j.1465-3362.2011.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for pregnancy: What's an acceptable risk, and how is the evidence (finally) shaping up?

Abstract: The policy advice that 'the safest choice for pregnant women is to abstain from alcohol during pregnancy' should be maintained. However, the abstinence message needs to be presented in a balanced and rational manner to prevent unintended negative consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 116 publications
1
105
0
1
Order By: Relevance
“…A recent finding from a large population-based study found variants in genes involved in alcohol metabolism among children and mothers who had drunk in moderation during pregnancy, associated with lower cognitive ability in the children at the age of 8 years. 144 This suggests that in some cases even small amounts of alcohol in utero can affect future cognitive outcomes, leading some authors to conclude that we may never be able to conclusively prove whether or not there are safe levels of alcohol consumption in pregnancy, making it morally and ethically unacceptable to suggest otherwise, [143][144][145][146][147] a message at odds with current UK guidelines.…”
Section: Effects Of Light To Moderate Drinking In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent finding from a large population-based study found variants in genes involved in alcohol metabolism among children and mothers who had drunk in moderation during pregnancy, associated with lower cognitive ability in the children at the age of 8 years. 144 This suggests that in some cases even small amounts of alcohol in utero can affect future cognitive outcomes, leading some authors to conclude that we may never be able to conclusively prove whether or not there are safe levels of alcohol consumption in pregnancy, making it morally and ethically unacceptable to suggest otherwise, [143][144][145][146][147] a message at odds with current UK guidelines.…”
Section: Effects Of Light To Moderate Drinking In Pregnancymentioning
confidence: 99%
“…Since 2009, the Australian government has advised women to abstain, a move away from previous guidelines which suggest that, if they chose to drink, they should consume fewer than seven drinks per week and never more than two drinks on the same day, and never get drunk. 146 In the UK before 2008, NICE suggested that pregnant women limit alcohol consumption to no more than one standard unit per day. Currently, pregnant women and women planning a pregnancy are advised to avoid drinking alcohol in the first 3 months of pregnancy if possible, because this may be associated with an increased risk of miscarriage.…”
Section: International and Uk Guidelines On Alcohol And Pregnancymentioning
confidence: 99%
“…The evidence for "low to moderate" prenatal alcohol exposure is mixed and overall unconvincing (13)(14)(15)(16)(17). The outcomes studied, including child behavioral problems and learning disorders, are nonspecific to alcohol and often subjectively evaluated through parent or teacher reports.…”
Section: Introductionmentioning
confidence: 99%
“…In some populations, moderate drinkers have higher education, higher income, better mental health, and stronger social networks than alcohol abstainers or heavy drinkers (19,20), factors that may also be associated with good parenting and positive child outcomes. Some of these attributes are not easily captured by available socio-demographic variables, and it has been suggested that residual confounding could obscure the detrimental effects of lower-level prenatal alcohol exposure or bias results in the opposite direction (17,21). Besides the possibility of biases and confounding, methodological weaknesses of these studies include small sample size and inadequate statistical power, lack of an unexposed referent group, and inadequate alcohol measures (lacking timing or pattern) (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation